Soft particles in an electric field – a zero average contrast study. Issue 31 (15th July 2019) - Nöjd, Sofi; Hirst, Christopher; Obiols-Rabasa, Marc; Schmitt, Julien; Radulescu, Aurel; Mohanty, Priti S.; Schurtenberger, Peter
Abstract : Small-angle neutron scattering experiments on microgels provide information about the response of the individual particles to an external electric field. Abstract : We report on the structural properties of ionic microgel particles subjected to alternating electric fields, using small-angle neutron scattering. The experiments were performed under so-called zero average contrast conditions, which cancel the structure factor contribution to the scattered intensity, allowing us to obtain direct information on the single particle size and structure as particles align in field-induced strings. Our results reveal only a marginal compression of the particles as they align in strings, and indicate considerable particle overlap at higher field strengths. These findings provide further insight into the origins of the previously reported unusual path dependent field-induced crystal-crystal transition found for these systems (P. S. Mohanty et al., Phys. Rev. X, 2015, 5, 011030).